KONSEP KEPEMIMPINAN MENURUT SYU’BAH ASA - Munadzir Munadzir (UIN Raden Mas Said Surakarta, 2017)
The discourse of leadership in Islam was emerged and developed after the passed away of prophet Muhammad Pbh. Alquran has connected the concept of leadership to the guidance of the truth. A leader must know the situation and able to feel his follower misery directly. A leader must also have the ability over his followers, in term of knowledge and action, religious service, courageous and excellence, character, and behavior. This is library research which is characteristically descriptive-analysis and focused on the book entitled Dalam Cahaya Alquran: Tafsir Ayat-ayat Sosial Politik written by Syu’bah Asa related to the qur’anic verses on leadership. The result of the study showed that Syu’bah Asa has interpreted surah Alnisa’ 58 as the suggestion for the leader to be injustice and wise, while for each citizen have to obey their leader as advised by surah Alnisa’ ayat 59.